Meningkatkan Keterampilan Proses Sains Melalui Model Pembelajaran Problem Based Learning (PBL) pada Materi Biologi - Ramadhan, Ramadhan; Ningsih, Kurnia; Supartini, Sri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This research aimed to enhance the science process skills of the students through the implementation of the Problem Based Learning (PBL) teaching model in biology learning. This type of research was a classroom action research conducted in two learning cycles. Each learning cycle consisted of planning, implementation, observation, and reflection stages. The subjects of this research were 21 students from Class X.G at SMA Negeri 1 Pontianak for the academic year 2022/2023. The research data were obtained through testing techniques using instruments such as pre-test and post-test questions that reflected six aspects of science process skills: observing, interpreting observations, classifying, predicting, communicating, and formulating hypotheses. The data analysis results showed that there was an improvement in the students' science process skills for each measured aspect in both cycle I and cycle II. The average science process skill score for students in cycle I was 62.7, and in cycle II, it was 80.2. Therefore, the research results can be concluded that teaching using the Problem Based Learning (PBL) teaching model can improve students' science process skills in biology learning.